1990
DOI: 10.1083/jcb.111.3.1107
|View full text |Cite
|
Sign up to set email alerts
|

Use of DNA sequence and mutant analyses and antisense oligodeoxynucleotides to examine the molecular basis of nonmuscle myosin light chain kinase autoinhibition, calmodulin recognition, and activity.

Abstract: The first primary structure for a nonmuscle myosin light chain kinase (nmMLCK) has been determined by elucidation of the cDNA sequence encoding the protein kinase from chicken embryo fibroblasts, and insight into the molecular mechanism of calmodulin (CaM) recognition and activation has been obtained by the use of site-specific mutagenesis and suppressor mutant analysis. Treatment of chicken and mouse fibroblasts with antisense oligodeoxynucleotides based on the cDNA sequence results in an apparent decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
114
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(127 citation statements)
references
References 82 publications
13
114
0
Order By: Relevance
“…The removal of the calmodulin regulatory domain (DCaM mutant) generated a constitutively active kinase (i.e., a gain of function mutation). This is consistent with previous information on other well studied calmodulin-dependent kinases, in which the calmodulin-regulatory domain has inhibitory e ects on the kinase activity, relieved by binding to Ca 2+ / calmodulin (Shoemaker et al, 1990). DAP-kinase activity was abolished by the substitution of a conserved lysine by alanine residue within the kinase domain (K42A), thus generating an inactive kinase mutant with potential dominant-negative activity .…”
Section: Biochemistry Of Dap-kinasesupporting
confidence: 91%
“…The removal of the calmodulin regulatory domain (DCaM mutant) generated a constitutively active kinase (i.e., a gain of function mutation). This is consistent with previous information on other well studied calmodulin-dependent kinases, in which the calmodulin-regulatory domain has inhibitory e ects on the kinase activity, relieved by binding to Ca 2+ / calmodulin (Shoemaker et al, 1990). DAP-kinase activity was abolished by the substitution of a conserved lysine by alanine residue within the kinase domain (K42A), thus generating an inactive kinase mutant with potential dominant-negative activity .…”
Section: Biochemistry Of Dap-kinasesupporting
confidence: 91%
“…A double charge cluster reversal mutation where D l 18-El20 was also replaced by KKK yielded almost no activation of sk-MLCK (Weber et al, 1989). Shoemaker et al (1990) showed that for fibroblast MLCK (CaM binding sequence identical to sm-MLCK), the K, for the substrate peptide was higher in the presence of E84K or E120K mutant CaMs, but decreased to the same value as the wild type if a charge reversa1 RRK-EEE was introduced at the beginning of the CaM binding region. In the crystal structure of CaM with the sm-MLCK peptide, both E120 and El 14 in the C-domain interact with basic residues in the N-terminal region of the peptide (Meador et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…EC MLCK-1 exhibited substantial time-dependent p60 src -catalyzed incorporation of radioactive phosphate (Fig. 2), whereas p60 src -mediated 32 P incorporation did not occur in either MLCK-2, the EC MLCK splice variant, lacking the 69-amino acid stretch containing the p60 src consensus site, nor in SM MLCK, which completely lacks the novel N terminus (Fig. 2).…”
Section: In Vitro Phosphorylation Of Mlck Isoforms By P60mentioning
confidence: 99%
“…Phosphorylation of MLCK diluted in reaction buffer was started by adding 0.2 mM ATP, 10 Ci/ml [␥- 32 P]ATP and 75 units/ml recombinant p60 src kinase (Upstate Biotechnology, Inc., Lake Placid, NY; final concentrations). Synthetic MLCK-1 peptides were used for p60 src phosphorylation assays at 0.1 mg/ml final concentration.…”
Section: Phosphorylation Of Mlck By P60 Src In Vitromentioning
confidence: 99%